An In Vitro Study Comparing Of Fracture Resistance For Different Resin Cores Of Different Composition - علي عمر; ميسم خدام (Latakia University Journal -Medical Sciences Series, 2023)
Aim of study : This study evaluated the fracture resistance of four resin composite core build-up materials Different composition and viscosity , two types of high viscosity composites (Nanohybrid , Bulkfill) , and two types og low viscosity composites (DualCure , Bulkfill) to find out which one is better at building cores , And knowing the location of Bulkfill low viscosity composite among the three types of composites commonly used in the construction of cores.Material and Methods : (40) single-channel lower premolars were collected , converging in shape , length and size . After that, the teeth were cut above the cemento-enamel junction by (1) mm and root canal treatment was done and the teeth were restored with fibre posts. The teeth were divided into four groups, each group includes (10) teeth in which the core was built with one of the four types of composite used in the research, with a height of (5) mm and The teeth were cast in acrylic molds.The fracture resistance was determined using a universal testing machine with a crosshead speed of 1 mm/min at 1350 to the tooth axis until failure occurred .Results : The results of this research showed that there is no difference in the resistance to fracture between types of high viscosity composites (traditional Nanohybrid, Bulkfill), While there was a difference in the resistance to fracture in the low viscosity composite group (DualCure, Bulkfill), Bulkfill composite had less resistance to fracture. and the results showed no difference between the three types of composites: traditional high-viscosity Nanohybrid, high-viscosity Bulkfill, and low-viscosity DualCure.Conclusion: There is no difference in the resistance to fracture between and low-viscosity DualCure when used as a core building material, while the low-viscosity Bulkfill composite showed the lowest percentage of fracture resistance.